Penerapan Prinsip 5S untuk Mengurangi Waste Motion dalam Proses Layanan Galon R-Water - Fredy Sumasto; Sri Hasyib Saputri; Rifqi Syahputra Awani; Aldi Maulana; Kristofer Simanjuntak; Ahlan Ismono; Supardi (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
This research aims to reduce waste in the R-WaterFilling Service Small and Medium Enterprises (SMEs) by applying the principles of Lean Manufacturing, specifically 5S (Seiri, Seiton, Seiso, Seiketsu, Shitsuke). The main problem identified is the length of service time caused by waste, which often hinders the achievement of daily sales targets. Through the Lean Manufacturing approach, we mapped and identified waste through Value Stream Mapping and Process Activity Mapping. The results of Value Stream Mapping show that R-Water's service process lead time is 822.22 seconds. Waste identification revealed the existence of waste motion in filling gallons of water. Based on these findings, root cause analysis was conducted using the Lean Manufacturing 5 Whys approach. The improvement phase was based on the root cause and applied the 5S principles. This improvement's results significantly impacted, reducing the lead time to 750.2 seconds. This research makes an essential contribution to minimizing waste in the service process, which in turn improves operational efficiency and helps achieve set sales targets.